Técnicas asertivas para disminuir las conductas agresivas en los alumnos de quinto grado, unidad educativa “ciudad de Loja”, sección vespertina, Loja. 2016-2017. - Coello Yunga, Ruth Noemy (2018)
The assertive techniques are strategies that require learning, which have to combine with cognitive, emotional and behavioral aspects, likewise, these require practicing and training to be able to integrate them thoroughly; for this reason, it was decided to develop the present research work having as a general objective to implement assertive techniques to decrease the aggressive behaviors of the fifth year students, Unidad Educativa “Ciudad de Loja”, afternoon section, Loja. 2016-2017, This research was developed from a qualitative approach according to the pre-experimental and a cross-sectional design, the methods used were: the deductive scientific, analytic, synthetic and statistical which contributed to elucidate the different aspects of the research. It worked with 17 participants between the students and the teacher, attending to workshops to give a solution in part of the problem established in this investigation. The questionnaire AQ from Buss and Perry, reduced version from Vigil-Colet et al. (Published) was applied for the pre and post-test. The results in the pre-test, evidenced that 62,50% of the participants manifested high levels of physical aggressiveness; 50,00% of them expressed middle levels of verbal aggressiveness and anger; and 43,75% showed middle levels of hostility and through the application of the psych-educative intervention proposal about the assertive techniques to decrease the aggressive behaviors, it evidenced through the application of the post-test that the physical aggressiveness lessened to 18,75%, the verbal aggressiveness lessen to 31,25%, in addition, the anger to 18,75: and similarly in the aspect of hostility, it reduced to 25,00%. In conclusion, the application of the psych educative intervention proposal, achieved decreasing the aggressive behaviors, improving the self-control of each student.